Berberine Facilitates Extinction and Prevents the Return of Fear - Huang, Shihao; Zhou, Yu; Wu, Feilong; Shi, Cuijie; Yan, He; Chen, Liangpei; Yang, Chang; Luo, Yixiao (Frontiers in Pharmacology, 2022)
Exposure to a catastrophic event or intense stimulation can trigger fear memories, and the nightmare memories persist even over a lifetime. Exposure therapy is based on extinction memory and is widely used to treat fear-related disorders, but its effect on remote fear memory is modest. Berberine, an isoquinoline alkaloid derived from Coptis sp. or Berberis sp, has been recently reported to exert a diversity of pharmacological effects on the central nervous system (CNS), such as facilitating extinction of drug memory. Here, we explored the effect of berberine on extinction of fear memory using a classical context fear conditioning (CFC) paradigm. Twenty-four hours or 30 d after CFC training, mice were subjected to context extinction (10 d) to extinguish their behaviors, and treated with berberine intragastrically 1 h or 6 h after each extinction session, followed by reinstatement and spontaneous recovery tests. The results showed that intragastric administration of berberine 1 h after extinction significantly promoted the extinction of recent and remote fear memories, and prevented reinstatement and spontaneous recovery of extinguished fear in mice. These findings indicate that berberine combined with extinction training could serve as a promising novel avenue for the treatment of fear-related disorders.